Penerapan Metode PBL untuk Meningkatkan Minat dan Hasil Belajar Bahasa Indonesia pada Siswa Kelas VIII SMP Negeri 13 Surakarta - Mahadhika Wipradharma; Himma Qatrunada (JURNAL ILMIAH NUSANTARA, 2024)
This research was conducted to improve the quality of classroom teaching by applying the Problem-Based Learning (PBL) model. Data collection methods included observation sheets, learning interest questionnaires, and cognitive learning outcomes assessments. The results indicate that the majority of students exhibited high or moderate interest in learning, with percentages of 90% and 7% respectively. Only 3% of students showed low interest in learning. An increase in students' interest in learning was observed in the second cycle, with the percentage of students displaying high interest rising to 90%. Additionally, student learning outcomes improved, with the percentage of students successfully completing the cycle increasing from 80% in cycle 1 to 90% in cycle 2. In conclusion, this research demonstrates that the PBL model can enhance students' interest in learning as well as their learning outcomes.